LITERACY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS: A MEANS OF BUILDING STUDENT CHARACTER IN THE DIGITAL ERA - Rawanita, Mesi; Zubaidah, Zubaidah; Khairan, Khairan (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
The digital revolution has brought significant changes to the world of education, including Islamic Religious Education, requiring teachers to master digital literacy, pedagogy, and content. This study explores teacher literacy's impact on character development in Islamic Religious Education during the digital era. Using a qualitative approach with a library research method, this study analyzes literature on teacher literacy, character education, and educational technology. The findings indicate that teachers' digital literacy influences teaching quality and the effectiveness of character education. Teachers with high digital literacy can leverage digital tools to create interactive and meaningful learning experiences. In contrast, those with low digital literacy tend to rely on traditional methods less relevant to students' needs in the digital age. Key challenges identified include limited access to technology, lack of digital literacy training, and cultural resistance to modern technology. This study recommends continuous training, the provision of technological infrastructure, and curriculum development that integrates Islamic values with digital approaches to enhance the effectiveness of character education.